Neutrophil gelatinase-associated lipocalin and interleukin-6: Potential biomarker for asthma- COPD overlap, differentiation from asthma and COPD. Issue 1 (1st January 2021) - Mihaylov, Miroslav; Bilyukov, Radoslav; Hristova, Julieta; Dimitrova, Denitsa; Youroukova, Vania
Abstract: Asthma-COPD overlap (ACO) is a disorder that combines clinical signs of bronchial asthma and COPD – fixed airways obstruction and/or significant reversibility of the bronchial obstruction, rapid progression, poor quality of life, higher mortality, frequent and severe exacerbations compared to COPD and asthma alone. The aim of our study is to determine the neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-6 (IL-6) plasma levels and to analyze their association with peripheral eosinophilia and exacerbations of patients with asthma-COPD overlap (ACO), Chronic obstructive pulmonary disease (COPD) and asthma. Our results, based on 81 patients, indicate that the plasma levels of NGAL and IL-6 are significantly elevated in ACO and are associated with blood eosinophilia and exacerbations. NGAL and IL-6 may be useful biomarkers for differentiation of patients with frequent exacerbations and ACO.